Analisis Kepuasan Masyarakat Pada Layanan SIM Online Menggunakan Metode SERVQUAL di SATLANTAS POLRES Garut - Nurul Kiftiyah (E-Jurnal Universitas Samudra, 2026)
Public service is a key responsibility of the government in meeting citizens’ needs. In the digital era, service quality is assessed not only by speed and accuracy but also by public satisfaction. One such innovation is the Online Driving License (SIM Online) service, introduced by the Indonesian National Police through Satlantas. While designed to simplify license issuance and renewal, its effectiveness must be evaluated.This internship research analyzes the service quality of SIM Online at Satlantas Polres Garut using the SERVQUAL method, covering Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data were collected from 100 respondents through questionnaires, supported by observation and short interviews.The results show an average expectation score of 4.62 and a perception score of 4.18, with a gap of -0.44, indicating the service has not fully met expectations. The largest gap lies in Responsiveness (-0.55), while the smallest is in Assurance (-0.35).In conclusion, SIM Online has improved service accessibility, but several aspects need enhancement, particularly responsiveness. These findings provide input for Satlantas Polres Garut to improve digital-based public services.